Determination of Quality outcome indicators in National Quality Assurance Standards (NQAS) accredited Hematology and Clinical Pathological laboratory - Desai, Killol Nathubhai; Menapara, Chiragkumar B (Annals of Pathology and Laboratory Medicine, 2019)
Background: Laboratory plays a vital role in disease control and prevention by providing timely data or information for patient management and disease surveillance. Quality in laboratory has huge impact on diagnosis and patient management as about 80% of all diagnosis is made on the basis of laboratory tests. Methods: The study was conducted in Central Diagnostic Laboratories of GMERS Medical College, Junagadh which is NQAS (National Quality Assurance Standards). The hospital uses internet and data is retrieved by the systems department. The study was conducted from January 2015 to December 2018. A total of 2,13,476 samples were received in the hematology and clinical pathology section. Different quality outcome indicators of hematology and clinical pathology laboratory were studied. Result: All Quality parameters were consistently improved from 2015 to 2018 due to new instrumentation, IQC, EQC, timely instrument maintenance, laboratory information system (LIS), telephonic communications and monthly-yearly quality improvement meetings. Some important indicators like TAT, critical alert were not reach up to the target value but due continuous improvement plane we soon reach target level. Conclusion: The concept of quality indicators has revolutionized the field of laboratory medicine. These indicators are of most importance in the comparison of individual laboratory performance with the aim of improving laboratory services and quality.